2021
DOI: 10.7150/ijbs.59374
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of global asymptomatic SARS-CoV-2 infection and management practices from China

Abstract: With ongoing research, it was found that asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was widespread in coronavirus disease 2019 (COVID-19) populations. Studies have confirmed asymptomatic patients with COVID-19 have potential infectivity, and most of the transmission occurred before symptoms appear. Asymptomatic infection rates varied widely in different countries and regions. Identifying the asymptomatic infected persons and cutting off the infection source is an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The result has a high accuracy (95.11%), which will be helpful for predicting the epidemic of SARS-CoV-2. With the development of the epidemic, many studies have shown that many COVID-19 patients have no symptoms but can spread the virus to others ( Kronbichler et al, 2020 ; Chen et al, 2021 ; Ralli et al, 2021 ). In the early stages of the epidemic, the proportion of symptomatic outcomes was high ( Bi et al, 2020 ) and gradually declined with the epidemic of SARS-CoV-2 according to the predicting result of our model.…”
Section: Discussionmentioning
confidence: 99%
“…The result has a high accuracy (95.11%), which will be helpful for predicting the epidemic of SARS-CoV-2. With the development of the epidemic, many studies have shown that many COVID-19 patients have no symptoms but can spread the virus to others ( Kronbichler et al, 2020 ; Chen et al, 2021 ; Ralli et al, 2021 ). In the early stages of the epidemic, the proportion of symptomatic outcomes was high ( Bi et al, 2020 ) and gradually declined with the epidemic of SARS-CoV-2 according to the predicting result of our model.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is necessary to continuously improve capabilities for precise and timely identification and rapid response for multi-point triggers of epidemic outbreaks. Three core capabilities include: the capability to quickly trace contacts, such as by using digital technologies for contact tracing [ 17 ]; the capability to rapidly provide nucleic acid detection [ 18 ], such as through large-scale nucleic acid detection for entire regions in a short time; and finally, the capacity for the admission and treatment of critically ill patients [ 19 ], such as ICU capacity and health capabilities in a particular area. The range of nucleic acid detection for screening should be determined by the identification of contacts and by focal points found in epidemiological COVID-19 investigations.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to an elevated population awareness of the COVID-19 pandemic, behavioural modification in response to government measures and the boosted capacity for SARS-CoV-2 nucleic acid testing during the second wave [ 9 ]. A role for large-scale PCR-based testing strategies in epidemic control during the second wave should be highlighted, as it is conducive for the detection of presymptomatic and asymptomatic cases [ 10 ]. Comprehensive and active PCR testing strategies implemented for key populations and in outbreak settings have ensured timeliness of early case detection and containment of local outbreaks [ 11 ].…”
Section: Discussionmentioning
confidence: 99%